2011
DOI: 10.1080/03634523.2010.516395
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oral Communication: A Major Review of the Historical Development and Trends in the Movement from 1975 to 2009

Abstract: This comprehensive review of the assessment of oral communication in the communication discipline is both descriptive and empirical in nature. First, some background on the topic of communication assessment is provided. Following the descriptive background, we present an empirical analysis of academic papers, research studies, and books about assessing communication, all of which were presented or published from 1975 to 2009. The results are outlined of content and thematic analyses of a database of 558 citati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It remains to be seen if this instrument will be adopted nationally. Morreale, Backlund, Hay, and Moore's (2011) metareview of oral communication assessment provided an excellent summary of the state of the discipline at this time. Their findings indicated that we have established definitions and the what-and-how of assessment.…”
mentioning
confidence: 99%
“…It remains to be seen if this instrument will be adopted nationally. Morreale, Backlund, Hay, and Moore's (2011) metareview of oral communication assessment provided an excellent summary of the state of the discipline at this time. Their findings indicated that we have established definitions and the what-and-how of assessment.…”
mentioning
confidence: 99%
“…The lack of validated measurement instruments in the included studies reveals a pressing issue in the science communication training literature. Yet, outside of the (relatively new) field of science communication, communication scholars and training/development researchers have well-established measures for evaluating oral communication skills (Dunbar et al, 2006; Morreale et al, 2011; Pearson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Morreale et al . () call communication a ‘process skill’ that needs to be assessed in authentic situations (p. 259). They also point out that communication is in some sense subjective: there is no one correct answer or way of performing.…”
Section: Aligning Goals Pedagogy and Assignments To Teach Transferamentioning
confidence: 99%